The Effect of Cu-doping on the Optical Properties of ZnFe2O4 Films Prepared by Chemical Spray Pyrolysis Method - Salim Azara Hussain (Journal of Global Pharma Technology, 2018)
In this work, the effect of the copper doping on Optical properties of zinc Ferrite precipitated on the glass Substrate of quartz, with  ratios of Cu (x= 0,0.1,0.3,0.5,0.7,0.9) using the method of chemical spray Pyrolysis of thickness(300 ± 15nm) at a temperature (400 ± 10 oC) and annealing (520 oC) for range of (4h) the Optical properties have been identified of films wavelengths of (300-900) nm , it has been found that the energy gap before doping(2.86 eV) the energy gap increased to increase the proportion of doping the ratios (x=  0.1,0.3, 0.5) the energy gap at ratios (x= 0.7 ,0.9) also found that the highest value of the coefficient of absorption at the ratio (x=0 .9) and the value of(3x104).Keywords: Absorption factor, Optical conductivity, Energy gap, Deflection.